(untitled) (Journal of Hama University, 2022)
Breeding chickens is one of the main components of animal agricultural activity, It effectively contributes to nutrition security for the population and contributes to greater self-sufficiency of animal products. Salamieh area with its dry climate is suitable for this poultry farming. The research aimed to identify the most important factors affecting the productivity of chicken meat in summer and winter cohorts, based on a simple random sample questionnaire form involving 111 chicken breeders in Salamieh area collected in 2020. For the winter cohort, the results showed that the change in the amount of feed and the amount of diesel used in the same cohort had a big moral impact on the amount of production, when there was an increase in feed consumption by (1) ton, the production of chicken meat increased by (0.414) tons, and when the diesel consumption increased by (1) liter, meat production increased by 6 kg or (0.006) tons. On the other hand, for the summer cohort, the change in the amount of the litter and the number of birds had a big moral impact on the amount of production where the increase in the amount of the litter by (1) ton increased the production of chicken meat by (7,022) tons, and by increasing the number of birds by (1) bird, the production of chicken meat increased by 1 kg or (0,001) tons.